Underpotential Deposition From Fundamentals and Theory to Applications at the Nanoscale - Oviedo, Oscar Alejandro; Reinaudi, Luis.; Garcia, Silvana; Leiva, Ezequiel Pedro Marcos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
With this volume, Ezequiel P. M. Leiva and co-authors fill a gap in the available literature, by providing a much-needed, comprehensive review of the relevant literature for electrochemists, materials scientists and energy researchers. For the first time, they present applications of underpotential deposition (UPD) on the nanoscale, such as nanoparticles and nanocavities, as well as for electrocatalysis. They also discuss real surface determinations and layer-by-layer growth of ultrathin films, as well as the very latest modeling approaches to UPD based on nanothermodynamics, statistical mechanics, molecular dynamics and Monte-Carlo simulations.
Introduction -- Phenomenology and Thermodynamics -- Structure of the UPD Phase -- Applications of UPD on Bulk Electrodes as a Model System -- Modelling of Underpotential Deposition on Bulk Electrodes -- UPD at the Nanoscale: Theory and Applications -- UPD: What is Coming Next?.
Keywords: Electrochemistry; Surfaces (Technology).; Thin films; Energy storage; Surfaces (Physics).; Microtechnology; Microelectromechanical systems; Electrochemistry; Surfaces, Interfaces and Thin Film; Mechanical and Thermal Energy Storage; Surface and Interface and Thin Film; Microsystems and MEMS